Implementation and Performance Evaluation of Simultaneous PET/MR Whole-Body Imaging with Continuous Table Motion - Braun, Harald; Ziegler, Susanne; Lentschig, Markus G.; Quick, Harald H. (Journal of Nuclear Medicine, 2014)
In current PET/MR systems, the data acquisition paradigm is based on a multistation examination, imaging the patient from hip to head. This strategy has potential limitations, especially in terms of workflow and PET acquisition efficiency. In this work, the technical implementation of simultaneous PET and MR data acquisition with continuous table motion (CTM) is presented. PET and MR data acquired with CTM are evaluated in terms of image quality with respect to table motion speed.Phantom, volunteer, and patient data were acquired on an integrated whole-body PET/MR system. Phantom experiments were used to systematically quantify image quality parameters including signal-to-noise ratio, geometric distortions, and artifacts in PET and MR scans as a function of different table speeds. Volunteer scans (n = 4) allowed evaluation of CTM MR protocols in a realistic setting, and patient scans (n = 3) were obtained to validate the technique in a clinical workflow.In phantoms, PET image quality, signal-to-noise ratio, geometry, and artifact behavior were found not to be influenced by continuous table motion over the evaluated table motion speeds from 0.8 to 4.6 mm/s. This also holds true for PET patient data where acquisitions were performed with varying table speeds of up to 46 mm/s. For MR, in most scans image quality of CTM scans was found to be comparable to the identical sequence acquired in multistation mode; however, some sequence features (e.g., signal intensity normalization) with impact on MR contrast are currently missing for CTM MR sequences.Data acquisition with continuous table motion in the PET/MR versus multistation acquisition scheme provides data of comparable quality in both PET and MR. This new acquisition paradigm potentially can provide a higher flexibility in simultaneous PET and MR whole-body data acquisition and facilitate examination planning and PET/MR hybrid imaging workflow.
EVALuna2:10075

Radiotracer dose reduction in integrated PET/MR: implications from national electrical manufacturers association phantom studies - Oehmigen, Mark; Ziegler, Susanne; Jakoby, Bjoern W.; Georgi, Jens-Christoph; Paulus, Daniel; Quick, Harald H. (Journal of Nuclear Medicine, 2014)
With the replacement of ionizing CT by MR imaging, integrated PET/MR in selected clinical applications may reduce the overall patient radiation dose when compared with PET/CT. Further potential for radiotracer dose reduction, while maintaining PET image quality (IQ) in integrated PET/MR, may be achieved by increasing the PET acquisition duration to match the longer time needed for MR data acquisition. To systematically verify this hypothesis under controlled conditions, this dose-reduction study was performed using a standardized phantom following the National Electrical Manufacturers Association (NEMA) IQ protocol.All measurements were performed on an integrated PET/MR whole-body hybrid system. The NEMA IQ phantom was filled with water and a total activity of 50.35 MBq of (18)F-FDG. The sphere-to-background activity ratio was 8:1. Multiple PET data blocks of 20-min acquisition time were acquired in list-mode format and were started periodically at multiples of the (18)F-FDG half-lives. Different sinograms (2, 4, 8, and 16 min in duration) were reconstructed. Attenuation correction of the filled NEMA phantom was performed using a CT-based attenuation map template. The attenuation-corrected PET images were then quantitatively evaluated following the NEMA IQ protocol, investigating contrast recovery, background variability, and signal-to-noise ratio. Image groups with half the activity and twice the acquisition time were evaluated. For better statistics, the experiment was repeated 3 times.Contrast recovery, background variability, and signal-to-noise ratio remained almost constant over 3 half-life periods when the decreasing radiotracer activity (100%, 50%, 25%, and 12.5%) was compensated by increasing acquisition time (2, 4, 8, and 16 min). The variation of contrast recovery over 3 half-life periods was small (-6% to +7%), with a mean variation of 2%, compared with the reference setting (100%, 2 min). The signal-to-noise ratio of the hot spheres showed only minor variations over 3 half-life periods (5%). Image readers could not distinguish subjective IQ between the different PET acquisition setups.An approach to reduce the injected radiotracer activity in integrated PET/MR imaging, while maintaining PET IQ, was presented and verified under idealized experimental conditions. This experiment may serve as a basis for further clinical PET/MR studies using reduced radiotracer dose as compared with conventional PET/CT studies.
EVALuna2:10098